Impact of CYP2C19 polymorphisms on serum concentration of voriconazole in iranian hematological patients - Sholeh Ebrahimpour; Soha Namazi; Mehdi Mohammadi; Mohsen Nikbakht; Molouk Hadjibabaie; Hamidreza Taghvaye Masoumi; Ardeshir Ghavamzadeh (Wolters Kluwer Medknow Publications, 2017)
Objective: This study aimed to determine the portion of Iranian patients who attain therapeutic serum concentrations of voriconazole (VRCZ) following administration of fixed doses. In addition, the effect of CYP2C19 polymorphism on serum levels of VRCZ was also investigated. Methods: Forty-eight adult patients of Iranian origin with hematologic malignancies, who received VRCZ for treatment of invasive aspergillosis, were recruited into the study. Blood samples were drawn at day 4 of treatment to measure trough drug concentrations and determine genotyping of CYP2C19 polymorphisms of each patient. High-performance liquid chromatography method was used for measuring VRCZ serum level and CYP2C19 polymorphisms were conducted by Sanger sequencing. Demographic and clinical characteristics of patients alongside with CYP2C19 polymorphisms were assessed to determine the effective factor/s on VRCZ serum concentration. Findings: Seventy-three percent of patients achieved therapeutic serum concentrations of VRCZ with administration of usual fixed doses in clinical practice. There was no correlation between weight-adjusted dose and serum concentrations of VRCZ. Mean serum levels were significantly different neither in genders nor in routes of administrations. Extensive and ultrarapid metabolizers (URMs) comprised 48.7% and 21.6% study population, respectively. CYP2C19 polymorphism dramatically influenced the trough levels of VRCZ, so that all patients with subtherapeutic levels expressed URM phenotype. Conclusion: With respect to high incidence of URM phenotype in Iranian population, and observed association of this phenotype with sub-therapeutic levels in our study, performing therapeutic drug monitoring is strongly recommended for all patients.